Investment legislation and its impact on attracting foreign investments to Sudan During the period 1956-2013 - Mohamed, Khaled Abdel Aziz Hassan (Arab Journal for Sciences and Research Publishing, 2016)
The study examined the investment legislation issued in Sudan during the last period and the impact of attracting foreign investments. The legal framework for investment is one of the most important elements and elements of the attractive investment climate which helps in regulating the relationship between all parties to the investment process. The investment that was issued in Sudan and its effectiveness in attracting foreign investment and guarantees and facilities provided in them and their impact on increasing investment rates. The study dealt with the development of investment legislation in Sudan with its sectoral stages, which focused on issuing a law for investment in a specific sector, and the comprehensive phase of issuing a unified investment law covering all economic sectors, with study of the most important features and facilities provided in the Sudan. The study found that there was instability in the investment laws in the Sudan during the previous period and the convergence of periods of issuance and not keeping pace with local and global economic developments, which had a negative impact in the lack of flow Foreign investments in Sudan over the past years, which reflected negatively on increasing economic development in Sudan rates.